PENGARUH KEPEMIMPINAN TERHADAP KINERJA PEGAWAI NEGERI SIPIL DI KANTOR KECAMATAN TAGULANDANG KABUPATEN SITARO - Tatulus, Afny; Mandey, Jantje; Rares, Joyce (JURNAL ADMINISTRASI PUBLIK, 2015)
Abstract : The progress and setbacks of an organization depends on leadership qualities of a leader. Seen from the point of view of any leader is always placed on one very important point. The role of a leader in an organization or group is vital. Because in that role, a leader will help the organization to realize its vision and mission. the purpose of this research can be formulated as follows: To determine the effect of Leadership Influence on Performance of Civil Servants in the District Office District Tagulandang Sitaro. This is a descriptive quantitative research, which describes the relationship between variables to analyze numerical data using statistical methods through hypothesis testing. In this study took the entire population of employees at the District Office Tagulandang Sitaro Regency, North Sulawesi, which consists of 18 people. Results of simple correlation analysis showed that the leadership role positively and significantly correlated to the performance of an employee or significant influence with the power of 58.7%; meaning that developments in performance of 58.7% is determined or influenced by the leadership role. Keywords: Leadership, Performance